Academic Habitats? An Essay on Research Ethics - Kofoed, Jette (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
In this essay, I experiment with Lauren Berlant’s idea of ‘cruel optimism’ to explore how policies specifying responsible conduct of research within academia have effects that extend beyond efforts at establishing an untarnished university. Based on a feminist ethics of care, alongside experiences from teaching PhD students about research integrity and ethics, I unpack how culpability, vigilance and powerlessness surface. In this essay I then speculate: what would it entail to care? I suggest that there is a need to consider research ethics as an ethics that cares both for and about the university as a habitat.